WRITING ‘PRAVASI’ LIVES: NARRATIVE TECHNIQUES IN DEEPAK UNNIKRISHNAN’S TEMPORARY PEOPLE - Abdurahman AK; Roy P P (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The emerging writer Deepak Unnikrishnan has employed various experimental techniques in his award winning novel Temporary People. The aberration in narrative style and typographical violations symbolize fractured and torn apart life of the characters of the novel. The paper analyses the relevance of such narrative and typographical departures in connection with the experiences of the characters of the novel.